Project Based Learning (PjBL) Model: Elementary School Students' Social Studies Learning Outcomes - Ali, Zulrifqa Rofiqa; Idawati, Idawati; Suardi, Suardi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Social studies education not only provides factual knowledge but also equips students with a deep understanding of the social, cultural, and environmental realities in which they live. The project-based learning model has significant potential to enhance student learning activities, which in turn can positively contribute to social studies learning outcomes. Therefore, this study intends to examine the effect of the Project-Based Learning (PjBL) model on student learning outcomes in social studies. The research method used a quasi-experimental method with a nonequivalent control group design. The study population was fifth-grade students from nine elementary schools in Cluster I, Parangloe District, Gowa Regency. The sample was taken from elementary schools Inpres Pakkolompo and elementary schools Inpres Jenemadinging using a random sampling technique, with a total of 41 students. Data was collected through observation and objective tests, then analyzed using descriptive and inferential statistics. The results showed a significant effect of the implementation of the PjBL model on student activity, cooperative character, and learning outcomes. Based on the significance value (sig) obtained of 0.013, which is smaller than the commonly used alpha value (0.05), it was concluded that the implementation of the PjBL model significantly influenced learning outcomes. This study demonstrates the effectiveness of the project-based learning approach in improving student academic achievement. This study recommends the implementation of the PjBL model to increase student engagement and improve student learning outcomes in social studies in elementary schools.